2013
DOI: 10.1108/03684921311310567
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a cybernetic epistemology: elementary anticipatory systems

Abstract: Purpose -The purpose of this paper is to analyze how elementary anticipation, understood as anticipation of the repetition of one known pattern, can emerge out of sequence learning and how it can contribute to the behavioral options of goal-oriented systems. Design/methodology/approach -A functional approach is used to develop the necessary cybernetic structures of a subsystem for sequence learning that can additionally provide standards of anticipated patterns for future pattern matching. Based on that it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…We can show again that the content of short-term memory determines the behavioral options of a goal-orientated system at a point in time. We showed that already for pattern recognition and sequence learning systems (Nechansky, 2012a, b) as well as for elementary anticipatory systems (Nechansky, 2013). All these system can momentarily only act towards patterns temporarily held in short-term memory, while any other observed patterns cannot be recognized and therefore cannot serve as inputs in decision-rules to trigger actions.…”
Section: Complex Anticipatory Systemsmentioning
confidence: 93%
See 4 more Smart Citations
“…We can show again that the content of short-term memory determines the behavioral options of a goal-orientated system at a point in time. We showed that already for pattern recognition and sequence learning systems (Nechansky, 2012a, b) as well as for elementary anticipatory systems (Nechansky, 2013). All these system can momentarily only act towards patterns temporarily held in short-term memory, while any other observed patterns cannot be recognized and therefore cannot serve as inputs in decision-rules to trigger actions.…”
Section: Complex Anticipatory Systemsmentioning
confidence: 93%
“…We will argue below that this decision process can use the same bottom-up and top-down search to find candidates for anticipation and the same checking for evaluations, as we found for elementary anticipation (Nechansky, 2013). But here it requires repeated cycles of this searching and checking, till finally the most important (dangerous or useful) pattern can be selected for anticipation.…”
Section: Complex Anticipatory Systemsmentioning
confidence: 95%
See 3 more Smart Citations